Are Implant-Supported Monolithic Zirconia Single Crowns a Viable Alternative to Metal-Ceramics? A Systematic Review and Meta-Analysis - Liandra Constantina da Mota Fonseca; Daniele Sorgatto Faé; Beatriz Neves Fernandes; Izabela da Costa; Jean Soares Miranda; Cleidiel Aparecido Araujo Lemos (Ceramics)
This study aimed to evaluate prosthetic complications, implant survival rates, and marginal bone loss in implant-supported monolithic restorations compared to metal-ceramic restorations. The study was registered in PROSPERO (CRD420251022336) and conducted following the Cochrane Handbook for Systematic Reviews of Interventions and PRISMA guidelines. A systematic search was conducted in the electronic databases MEDLINE/PubMed, Web of Science, Scopus, Embase, and ProQuest for articles published up to December 2024. The inclusion criteria comprised studies evaluating only randomized clinical trials that evaluated implant-supported monolithic restorations directly compared to metal-ceramic restorations, considering any type of ceramic material and regardless of the fixation system (screw-retained or cemented), with a minimum follow-up of one year. A meta-analysis was performed using RevMan 5.4 software, and the risk of bias and certainty of evidence were assessed using the RoB 2.0 and GRADE tools, respectively. A total of six studies were included, all of which exclusively evaluated monolithic zirconia single crowns over follow-up periods ranging from 1 to 3 years. None of the included studies evaluated fixed partial dentures or restorative materials other than monolithic zirconia. In total, 267 patients (mean age range: 18–57 years) were analyzed, with a total of 174 implant-supported monolithic zirconia crowns and 165 metal-ceramic single crowns in the posterior region (premolars and molars). The meta-analysis revealed that implant-supported monolithic zirconia single crowns exhibited significantly fewer prosthetic complications compared to metal-ceramic single crowns (p < 0.0001; Risk Ratio [RR]: 0.26; Confidence Interval [CI]: 0.14–0.47). However, no statistically significant differences were observed between implant-supported monolithic zirconia and metal-ceramic single crowns regarding implant survival rates (p = 0.36; RR: 1.66; CI: 0.56–4.94) or marginal bone loss (p = 0.15; Mean Difference [MD]: −0.05; CI: −0.11–0.02). The risk of bias assessment indicated that four studies had a low risk of bias. However, the certainty of evidence was classified as low for prosthetic complications and implant survival rates and very low for marginal bone loss. Within the limitations of this review, it can be concluded that implant-supported monolithic zirconia single crowns can be considered a favorable treatment option as they show comparable implant survival and bone stability to metal-ceramic crowns, with a potential reduction in short-term prosthetic complications such as screw loosening and ceramic chipping. However, due to the limited number of studies included and low certainty of evidence, further long-term research is still needed to confirm their clinical performance over time.